2009
DOI: 10.1523/jneurosci.2294-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Prion Protein at Serine 43 Induces Prion Protein Conformational Change

Abstract: The cause of the conformational change of normal cellular prion protein (PrP) into its disease-associated form is unknown. Posttranslational modifications, such as glycosylation, acetylation, S-nitrosylation, and phosphorylation, are known to induce protein conformational changes. Here, we investigated whether phosphorylation could induce the conformational change of PrP because PrP contains several kinase motifs and has been found recently in the cytosol, in which kinases generally reside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 53 publications
(63 reference statements)
0
24
0
Order By: Relevance
“…Therefore we suggest an aggregation scheme (depicted in and outlined the host of far-reaching effects, either on molecular or on cellular levels. [19][20][21]25,[67][68][69] Our results demonstrated that Trp-cage miniproteins are sensitive models for studying the effect of phosphorylation on aggregation and amyloid formation, exhibiting highly site-specific effects, in some cases facilitating and in others by blocking amyloid fibrillization. (Table S1), Sequence analysis for amylidogenic regions of Trpcage (Fig.…”
Section: Ph Dependence Of the Aggregation Of D9s(p) And 13s(p) Trp-camentioning
confidence: 69%
“…Therefore we suggest an aggregation scheme (depicted in and outlined the host of far-reaching effects, either on molecular or on cellular levels. [19][20][21]25,[67][68][69] Our results demonstrated that Trp-cage miniproteins are sensitive models for studying the effect of phosphorylation on aggregation and amyloid formation, exhibiting highly site-specific effects, in some cases facilitating and in others by blocking amyloid fibrillization. (Table S1), Sequence analysis for amylidogenic regions of Trpcage (Fig.…”
Section: Ph Dependence Of the Aggregation Of D9s(p) And 13s(p) Trp-camentioning
confidence: 69%
“…Reaction-Previously, we have shown that the Cdk5-phosphorylated PrP was proteinase K-resistant and Congo Red-positive, and transmission electron microscopy revealed that Cdk5-phosphorylated PrP WT converted into aggregates composed of both anti-pPrP S43 immunopositive and immunonegative globules, which became compacted and generated rare fibrils with aging (15). The hyperbolic shape of the IKTA reaction with full-length wild type phosphorylated PrPs indicates a rapid conversion of these PrPs after Cdk5 phosphorylation (Fig.…”
Section: The Cdk5-phosphorylated Prp Wt-v Conversion Is Reversed Uponmentioning
confidence: 87%
“…The phosphorylated PrPs may convert irreversibly with time. We have shown by electron microscopy that aging of the phosphorylated wild type PrP resulted in a change from globular aggregates to a more compact structure (15). The increased rate constant of Cdk5-mediated PrP conversion in the familial PrP mutants may explain the age-dependent manifestation of the prion diseases associated with those mutations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations